Meningkatkan Pemahaman Strategi Pemasaran dan Penerapan Digital Marketing pada UMKM Dusun Mulyorejo: Studi Kasus pada Kelompok Usaha “Kinanti Snack” di Desa Limbung, Kecamatan Sungai Raya, Kubu Raya - Safitri, Dayang Annisa; Daud, Ilzar; Sudjono, Denzel; Fajryn, Marleny; Dinata, Febtian Aaron (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Small and Medium Enterprises (SMEs) play a strategic role in Indonesia's economy, but one of the main challenges they face is the limited scale of marketing, particularly in utilizing digital technology. This Community Service Program (PKM) aims to improve the understanding and implementation of digital marketing strategies for SMEs, specifically for the business